Power consumption and thermal performance of integrated spray and jet array cooling vapor chambers - Yi, Li (2022)
An integrated arrayed spray impingement vapor chamber (ISVC) is designed for cooling high-power electronic devices. The spray array is arranged on the vapor chamber to measure thermal performance in comparison with the other two integrated arrayed jet impingement vapor chambers (IJVCs) with different jet orifice diameters, named IJVC-0.8 and IJVC-3.0, on the basis of the inlet and outlet diameters of the spray nozzles. Tests have been conducted on pressure drop, power consumption, heat dissipation performance, temperature uniformity, and comprehensive performance. Results show that the pressure drop and power consumption of IJVC-0.8 and IJVC-3.0 are 1.36–1.53 and 0.079–0.09 times those of ISVC. In addition, the heat dissipation performance and temperature uniformity of the ISVC are better than those of IJVCs for given tests conditions. Furthermore, the heat dissipation of ISVC shows more advantage than those of IJVCs as the power is increased. Finally, the comprehensive performance of ISVC is revealed to be superior to that of IJVC if the exit apertures of the spray nozzles and jet holes are equal in diameter. In the IJVCs, choosing larger jet holes is to sacrifice part of the heat dissipation capacity, but compensate for the detrimental effects of high pressure drop, and subsequently improve its overall performance.